Effects of dietary administration of fenugreek seeds on metabolic parameters and immune status of gilthead seabream (Sparus aurata L.). Issue 74 (March 2018) - Guardiola, F.A.; Bahi, A.; Esteban, M.A.
Abstract: Medical plants could be used as a prophylactic method in aquaculture because they are considered safe and so very promising alternatives to the use of chemicals. The aim of the present work was to examine the effects of dietary fenugreek ( Trigonella foenum graecum ) seeds administered for 8 weeks on the metabolic and immune status of gilthead seabream ( Sparus aurata L.). Four experimental groups were designated: one receiving a basal diet (control) and three fed powdered fenugreek seeds incorporated in the fish feed at 1%, 5% and 10%. The results show that significant decreases in aspartate aminotransferase, creatine kinase, potassium and the albumin/globulin ratio were detected in the serum of fish fed 10% fenugreek compared with the values recorded in control fish. As regards the immune status, fish fed the 5% supplemented diet had higher haemolytic complement and peroxidase activities than the control fish whilst antiprotease activity was higher in fish fed the 1% fenugreek level respect to control fish and the fish fed the highest fenugreek supplementation rate. Interestingly, the results also revealed a significant enhancement of most of the cellular immune parameters studied, especially in fish fed the highest level of fenugreek (10%). However, the bacteriostatic activity of serum against fish pathogenic and non-pathogenic bacteria was non-affected to any significant extent in fish fed the supplemented diets. Overall, the results suggest that the high level of dietary fenugreek tested in this work (10%) did not negatively affect any of the metabolic parameters measured in serum but increased some of them. In addition, the inclusion of fenugreek seeds in the gilthead seabream diet at 5% or 10% improved the humoral and cellular immune activities, respectively. Further studies are needed to better understand the effects of this natural product, which may be suitable for use as a feed additive in fish aquaculture. Graphical abstract: Image 1 Highlights: Dietary supplements of fenugreek seeds for 8 weeks has beneficial effects in gilthead seabream. Fenugreek incorporation (10%) do not impact negatively to any of the 10 metabolic parameters tested. Fenugreek administration improved some of the seabream metabolism parameters evaluated. Seric complement and peroxidase activities were increased in fish fed 5% supplemented diet. The highest inclusion of fenugreek tested (10%) enhance the cellular innate immunity.